전담간호사의 직무 스트레스, 감정노동과 긍정심리자본이 직무만족도에 미치는 영향 - 홍보람; 김경미 (한국직업건강간호학회지, 2019)
Purpose: The purpose of this study was to identify the effects of job stress, emotional labor, and positive psychological capital on the job satisfaction of physician assistants (PAs). Methods: The sample consisted of 166 PAs working in general hospitals in B city, Y city, and C city. Data were analyzed through the SPSS/WIN 18.0 program using t-test, ANOVA, Scheffé test, Pearson's correlation coefficients, and multiple regression. Results: The factors of job stress (β=-.488, p<.001), positive psychological capital (β=.188, p=.004), and total clinical career (β=-.147, p=.014) had the greatest influence on the level of job satisfaction experienced by the PAs. The total explanatory power was 49.9%. Conclusion: It was found that job stress, positive psychological capital, and total clinical career were influencing factors in the job satisfaction of PAs. Therefore, to improve their job satisfaction, it is necessary to develop strategies to manage the job stress experienced by PAs, and to strengthen and develop positive psychological capital.